Failure Analysis Of Water Pump Shaft - Ariwibowo, Didik; Putra, Sulthonul; Darmanto, Seno; Mrihardjono, Juli; Mangestiyono, Wiji (Journal of Vocational Studies on Applied Research, 2019)
A water pump shaft for utility water raw material was failed. The shaft was broken into two parts. While in dismantling, the sand was found in chamber between bearing and shaft. There was also a bolt in the impeller. According to reports, the pump has been repaired and since there was no replacement shaft but the shaft was reused in reverse position. There was no inspection of the shaft when it was disconnected by operational reasons. The failure analysis of the broken-shaft was performed to investigate the cause of the failure. Two inspection and analysis were perfomed those are visual inspection and material identification and analysis. When material analysis of the shaft was carried out there was difference between examination and data specification of the shaft.The material identification indicate that the material was AISI SS 304 whereas specification data states SS 316. Both materials have similar tensile stress, so the difference was not the contributor of the failure. The present of foreign material was consider as the cause of the failure. The foreign material caused to stucked on rotation of shaft and increasing in tensile of the shaft over its ultimate strength.